2019
DOI: 10.1186/s12871-019-0788-5
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuated TNF-α-modulated occludin expression by inhibiting Hif-1α/ VEGF/ VEGFR-2/ ERK signaling pathway in hCMEC/D3 cells

Abstract: Background: The levels of tight junction proteins (TJs), especially occludin, correlate with blood-brain barrier (BBB) disruption caused by inflammation in central nervous system (CNS). It has been reported that propofol, the most commonly used anesthetic, could inhibit inflammation response in CNS. In this study, we investigated the effects of tumor necrosis factor-α (TNF-α) and propofol on occludin expression in human cerebral microvascular endothelial cell line, D3 clone (hCMEC/D3 cells), and explored the u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…Neuroinflammation has been considered as a major pathogenesis of POCD, through exerting noxious effects on neurons, synapsis and BBB 3‐5 . Previous studies have revealed that pro‐inflammatory cytokine TNF‐α may induce dopaminergic neuron apoptosis, deteriorate brain microglia and astrocyte function, modulate synaptic plasticity and impair neuronal tight junction as well BBB integrity 9‐13,30 . Hippocampal neurons play important roles in learning and memory, and excessive hippocampal neuron autophagy was revealed to be extensively involved in the development of POCD 15,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation has been considered as a major pathogenesis of POCD, through exerting noxious effects on neurons, synapsis and BBB 3‐5 . Previous studies have revealed that pro‐inflammatory cytokine TNF‐α may induce dopaminergic neuron apoptosis, deteriorate brain microglia and astrocyte function, modulate synaptic plasticity and impair neuronal tight junction as well BBB integrity 9‐13,30 . Hippocampal neurons play important roles in learning and memory, and excessive hippocampal neuron autophagy was revealed to be extensively involved in the development of POCD 15,31 .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α and IL-1β activate the p38/ERK1/2 pathway and increase myosin light chain kinase [ 59 ]. TNF-α also activates the Hif-1α/ VEGF/ VEGFR-2/ ERK signaling pathway to decrease the expression of occludin in human cerebral microvascular endothelial cell lines [ 60 ]. IL-6 is a pleiotropic cytokine with both proinflammatory and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increased inflammatory response and TNF- α levels may exacerbate brain injury, inhibit stimulation of neurogenesis, and cause neuroinflammation and blood-brain barrier disruption [ 3 ]. Also, TNF- α has a physiological role in synaptic transmission and plasticity in the healthy central nervous system, but increased TNF- α levels have an inhibitory effect on glutamate transporters, resulting in increased glutamate concentration and excessive toxicity [ 35 ]. The expression of mTNF- α (a precursor of TNF- α ) in microglia cells increases during propofol anesthesia and may mediate propofol-induced neurotoxicity and cognitive impairment in surgical or critically ill patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%